IT as an enabler of sustainable use of data from innovative technical components for assisted living - Knaup-Gregori, Petra; Schöpe, Lothar (Quality of life through quality of information, 2012)
The authors see the major potential of systematically processing data from AAL-technology in higher sustainability, higher technology acceptance, higher security, higher robustness, higher flexibility and better integration in existing structures and processes. This potential is currently underachieved and not yet systematically promoted. The authors have written a position paper on potential and necessity of substantial IT research enhancing Ambient Assisted Living (AAL) applications. This paper summarizes the most important challenges in the fields health care, data protection, operation and user interfaces. Research in medical informatics is necessary among others in the fields flexible authorization concept, medical information needs, algorithms to evaluate user profiles and visualization of aggregated data.